PENERAPAN SISTEM AKUNTANSI BIAYA UNTUK MENINGKATKAN TINGKAT AKURASI BIAYA PRODUKSI (STUDI PRAKTIK KERJA PADA PT HAMPARAN PLASTINDO RAYA) - KURNIAWAN, DAVID (JURNAL ILMIAH MAHASISWA AKUNTANSI, 2012)
Cost accounting is the process of recording, classifying and presenting the costs of production and sale of products or services in a particular way. PT Hamparan Plastindo Raya does not have accurate cost accounting system in determining the cost of production, especially in terms of cost classification. This can affect the quality of cost information and less precise decision-making. This study sought to apply the cost accounting system in order to obtain more accurate cost information, especially about the Cost of Goods Manufactured. Cost of Goods Manufactured can be useful to determine the selling price of the product, monitor production costs and calculate the periodic income. Hence the importance of accuracy of cost information, calculations in this study was made as close as possible to the actual condition of the company. System of cost calculation in this study carried out by collecting the companies original data with some adjustments in order to reach a more precise calculation. The results of this study indicate that companies calculate the Cost of Goods Manufactured is too big rather than actual conditions. This is because the classification of costs that are not appropriate in calculating the Cost of Goods Manufactured and not done an adequate separation between the cost of office and production costs.